The Characteristics of Radial Growth and Ecological Response of Caragana korshinskii Kom. Under Different Precipitation Gradient in the Western Loess Plateau, China - Che, Cunwei; Xiao, Shengchun; Ding, Aijun; Peng, Xiaomei; Su, Jingrong (Frontiers in Plant Science, 2022)
Understanding the temporal-spatial variability of tree radial growth and ecological response is the basis for assessing forest vulnerability in sight of climate change. We studied stands of the shrub Caragana korshinskii Kom. at four sample sites that spanned the different precipitation gradient (180–415 mm) across China’s western Loess Plateau, and demonstrated its radial growth dynamics and ecological response in different climate regions. We found that the growth of natural C. korshinskii in arid regions have adapted and cope with regional environmental changes and radial growth was less affected by drought stress. However, the growth of planted C. korshinskii were significantly affected by drought stress in arid and semi-arid regions, especially during the growing season (from June to September). Variations in radial growth rates and growth indicators such as shrub height, canopy area are consistent with the climate-growth relationship. With increase of precipitation, the limiting of drought on the growth of planted C. korshinskii gradually decreased and the amount of radial growth variation explained by drought decreased from 53.8% to 34.2% and 22.3% from 270 to 399 and 415 mm of precipitation, respectively. In addition, the age-related radial growth trend indicate that radial growth increased to around 4 years of age, decreased rapidly until 12 to 14 years of age, and then tend to stabilized. In the context of climate warming and humidification, increased precipitation and regular branch coppicing management at around 12 years will help to retain soil moisture and mitigate the limitation of drought on the growth of C. korshinskii. Moreover, initial planting density should be tailored to local precipitation conditions (below 5000 shrubs per hectare). The above results have important practical significance for the maintenance of the stability and sustainable management of plantation forests in the western Loess Plateau.